ANALISIS SOAL CERITA BERKARAKTERISTIK HOTS DALAM PEMBELAJARAN MATEMATIKA BERBASIS DEEP LEARNING DI KELAS III SDN KEBALEN 01 - Syafitri Azahra; Husna Farhana; Sani Aryanto; Awiria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of story problems that focus on Higher Order Thinking Skills (HOTS) in mathematics learning using the Deep Learning approach in class III of SDN Kebalen 01. The method used in this study is a qualitative approach with a case study design. Data collection was carried out through observation and interviews with teachers and students, then the data was analyzed using a descriptive interpretive method. The results of the study indicate that teachers have implemented the principles of Deep Learning (mindful, meaningful, joyful) and technology in a contextual way, while inserting HOTS-characterized story problems at levels C4 to C6 that are appropriate to the stage of students' cognitive development. These problems have proven effective in encouraging students' ability to analyze, evaluate, and create in solving mathematical problems. This study shows that the combination of the Deep Learning approach and story problems included in the HOTS category is a powerful strategy for building deeper conceptual understanding and improving students' critical thinking skills.